Quality, chemical composition, and antioxidative activity of cananga (Cananga odorata) oil - Rini Pujiarti; Titis Budi Widowati; Kasmudjo Kasmudjo; Sigit Sunarta (Jurnal Ilmu Kehutanan)
Cananga oil in this study was obtained from fresh flowers of Cananga odorata by water-steam distillation. The result of physical properties of cananga oil were compared with the SNI 06-3949-1005 showed that cananga oil was satisfied the quality prescribed by standard. The chemical composition of cananga oil was analyzed by GC-MS. GC-MS analysis showed that 23 compounds have been identified. The main compounds of cananga oil were caryophyllene (36.44%), â-linalool (5.97%), á-caryophyllene (9.61%), germacrene D (17.23%) and benzyl benzoate (7.18%). The DPPH scavenging assay showed that cananga oil possess mild antioxidant activity (IC50: 2.29 mg/ml) if compared with positive control of BHA (IC50: 0.03 mg/ml). This study indicated that cananga oil has potency as mild natural antioxidant.